Investment Opportunity Set (IOS) Berbasis Pertumbuhan Perusahaan dan Kaitannya Dengan Upaya Peningkatan Nilai Perusahaan - Eka Handriani; Tjiptowati Endang Irianti (Jurnal Ekonomi dan Bisnis, 2015)
This research aims to develop theoretical approach to complete the conceptual controversy regarding the research results on the investment policy and firm value. This research employs firm value, investment opportunity set (IOS), funding and dividend as variables. Dividends in the research proxied by dividend pay out ratio (DPR), funding proxied by DER and firm value indicated by Tobin’s q, which are mediated by IOS. The sample are taken from 154 manufacturing company financial statements during 2010 to 2012. The data were tested using path analysis. The research found that dividend and funding policy positively influence IOS. Investment opportunity (IOS) positively influences the firm value. IOS was able to mediate the effect of dividends to the firm value, and also the influence of funding decisions to firm value.